THE STUDENTS’ EYESIGHT ON THE EFFECTIVENESS OF REMOTE LEARNING DURING THE COVID-19 PANDEMIC - Tsuraya, Annisa Shofa; Abubakar, Multazam; Muthi'ah, Muthi'ah (Journal of Islam and Science, 2021)
The world is paralyzed. In the beginning of 2020, the earth is attacked by COVID-19 pandemic. This pandemic has a massive impact towards all sectors in human daily life. All communication way shift to online communication include teaching and learning process. This research was aimed at evaluating the effectiveness of remote learning in the midst of a COVID-19 pandemic. This research applied qualitative method. The subject of this research are the English department students of a state university in Makassar, Indonesia. Open-response questionnaire was chosen as the instrument to gain the data. Thus, the pandemic of COVID-19, the researcher spread the questionnaire through Google Form. From the questionnaire, the result showed that the majority of students did not like remote learning. They did not enjoy the teaching and learning program such as discussion class or when they wanted to communicate with their friends and lecturers. There felt some obstacles in creating a real teaching and learning English condition through remote learning due to the unsupported device and unstable internet networks. It can be concluded that Indonesia has not ready yet to apply the remote learning as the standard learning system due to the uneven welfare and the spread of stable internet networks. This condition also possible drives students to some psychological disorders such as anxiety and under pressure. The lesson learned from this COVID-19 pandemic will make the next generation, remote learning platforms, and solutions for future cases more ready and better than today.